Food Waste Management in the Hospitality Industry: A Qualitative Exploration of Sustainable Business Practices at Alila Ubud - I Komang Bambang Putrawan; Dewa Made Suria Antara; I Ketut Budarma (International Journal Labs, 2026)
This study explores Food Waste Management (FWM) practices within the hospitality industry, focusing on Alila Ubud as a luxury boutique eco-resort in Bali. The growing tourism sector has escalated food waste generation, necessitating sustainable management strategies to optimize operational efficiency and environmental outcomes. The research aims to analyze FWM practices, identify challenges in their implementation, and examine their contribution to Sustainable Business Practices (SBP). A qualitative case study approach was employed under a constructivist paradigm, using purposive sampling to select key informants, including executive chefs, operational managers, and food and beverage staff. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using thematic analysis combined with triangulation to ensure validity. The findings indicate that Alila Ubud implements FWM through prevention, reduction, reuse, recycling and valorization, and disposal stages, forming a structured operational system. However, challenges persist in staff behavioral consistency, continuous training requirements, and reliance on third-party waste treatment. The study demonstrates that FWM contributes to SBP across environmental, economic, and social dimensions, while the integration of Tri Hita Karana values reinforces a holistic approach linking operational practices, managerial strategies, and local cultural ethics. Recommendations include formalizing standard operating procedures (SOPs), recording waste volumes, and continuous capacity building to strengthen FWM as a core sustainability strategy.